Current aspects of the clinic, diagnosis and treatment of acquired myasthenia gravis (review). Part 1: diagnostics - S. N. Bardakov; S. A. Zhivolupov; E. R. Barantsevich; M. V. Zakharov; I. N. Samartsev (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Acquired myasthenia gravis is an autoimmune disease, based on the imbalance of humoral and cellular immunity, characterized by weakness and fatigue of skeletal muscles, and in some cases involvement of the heart muscle. In most cases, the object of the autoimmune destruction is peripheral nicotinic acetylcholine receptors of the postsynaptic membrane of the neuromuscular synapse. In myasthenia gravis there has been identified a number of other antigenic targets: muscle-specific tyrosine kinase, lowdensity lipoprotein receptor-related protein 4, titin, and ryanodine receptors skeletal muscles. Their specificity and pathogenetic role have been disclosed, but it is about 15-20% of seronegative forms that require further immunological research. Accurate diagnosis depends on the efficient detection of clinical forms of myasthenia gravis and full analysis of the autoimmune mechanisms underlying the disease.